Effectiveness of Public Complaints Commission As Alternative Dispute Resolution Mechanism In Nigeria - Amos Ojo Adedeji (Journal of Multidisciplinary Science, 2022)
The institution of ombudsman has become a global phenomenon, permanent and inevitable in the political system. Some administrative agencies in Nigeria are becoming aware of the important role the institution is playing and have therefore developed interest in the institution by according it some degree of cooperation. The study investigate the effectiveness of Public Complaints Commission as Alternative Dispute Resolution mechanism in Nigeria. Both quantitative and qualitative research design were adopted which relied on the administration of questionnaire to elicit information. The findings shows that the commission has recorded great achievements since inception such as decongestion of courts, checks against jungle justice, defender of common man’s rights among others. Despite these laudable impacts, the study revealed that the relevance of the commission is being challenged by a number of threats such as structural deficiency, poor funding and shortage of qualitative manpower to mention a few. The study concluded by recommending employment of qualified manpower, financial autonomy and political neutrality of the commission. The commission will only be effective in its constitutional roles when the act that established it is amended to remove all unnecessary restrictions from the power of the commission.